2014
DOI: 10.1088/1054-660x/24/10/105116
|View full text |Cite
|
Sign up to set email alerts
|

Tunable microwave output over a wide RF region generated by an optical dual-wavelength fiber laser

Abstract: The dual-wavelength fiber laser provides a compact, robust and stable platform for the generation of microwave signals. Two approaches towards generating microwave emissions using dual wavelengths are explored in this work, with both exploiting the heterodyning beat technique. Both approaches are based on a ring fiber laser with an erbium-doped fiber, having absorption coefficients of 16.0-20.0 dBm at 1531 nm and 11.0-13.0 dBm at 980 nm, serving as the active gain medium. A 10 cm long photonic crystal fiber wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The use of PCF brings advantages of flexibility and wavelength-dependent characteristics, thus making the material an almost ideal choice as a wavelength selective filter for TDFL. This work is synchronous with previous efforts to generate microwave signals from fiber optic elements for use in radio over fiber (ROF) applications, which are mentioned in 16 17 18 for the 1.5 μm region. The particular interest in the development of the 1.9 μm source is in anticipation of spectroscopic analysis applications of various gases, in particular for high sensitivity trace gas sensing of CO 2 , N 2 O, H 2 CO, and HBr 20 .…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The use of PCF brings advantages of flexibility and wavelength-dependent characteristics, thus making the material an almost ideal choice as a wavelength selective filter for TDFL. This work is synchronous with previous efforts to generate microwave signals from fiber optic elements for use in radio over fiber (ROF) applications, which are mentioned in 16 17 18 for the 1.5 μm region. The particular interest in the development of the 1.9 μm source is in anticipation of spectroscopic analysis applications of various gases, in particular for high sensitivity trace gas sensing of CO 2 , N 2 O, H 2 CO, and HBr 20 .…”
supporting
confidence: 66%
“…A large number of researchers have investigated the distinctive properties of photonic crystal fibers, such as wide range single mode operation, dispersion flexibility, large mode area and its application in multi-wavelength generation 14 15 16 17 . In most cases, those properties were proven to be wavelength dependent and equivalent to the behavior of wavelength-selective filters 18 19 .…”
mentioning
confidence: 99%
“…Dual wavelength fiber laser (DWFL) is one of the interesting approach to generate radio frequency (RF) signals at mm-wave frequencies 37 38 and terahertz sources 39 40 . Erbium doped fiber (EDF) is the most commonly used gain medium in fiber laser setup in regions of 1.5 micron including multi-wavelength laser.…”
mentioning
confidence: 99%
“…The capability of RoFSO is comparable with the radio over fiber (RoF), but there is a difference which is the omission of the fiber medium. Benefits from using high transmission capacity together with the ease of deployment associated with wireless links are the other differences . RoFSO has also found applications within indoor optical broadcasting.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits from using high transmission capacity together with the ease of deployment associated with wireless links are the other differences. 3,4 RoFSO has also found applications within indoor optical broadcasting. A practical research of indoor optical wireless link is shown in details in a report.…”
Section: Introductionmentioning
confidence: 99%